Nitrogen-containing and oxygen-rich lignin-based porous carbon and its preparation and application in carbon dioxide adsorption
Through the combined process of hydrothermal treatment and tablet heat treatment, the pore structure and surface chemistry of lignin-based porous carbon materials are regulated, and the problem of unsatisfactory CO2 capture performance of existing materials is solved, achieving efficient and low-cost CO2 capture effect.
Patent Information
- Application Number
- CN202310074440.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-01-18
AI Technical Summary
The carbon dioxide capture performance of the existing lignin-based porous carbon materials is not ideal, and there are problems such as high energy consumption, the use of toxic and high-cost reagents, and low CO2 adsorption.
The combination of hydrothermal treatment and tablet heat treatment is adopted, and the hydrothermal treatment is assisted by nitrogen source melamine, combined with the tableting and heat treatment of the activator, the pore structure and surface chemistry of the material are regulated, and the adsorption capacity and selectivity of CO2 are improved.
The prepared nitrogen-containing oxygen-rich lignin-based porous carbon material has a high specific surface area, excellent CO2 capture performance and good selectivity, is low in cost and environmentally friendly, and is suitable for industrial applications.
Smart Images

Figure CN116040629B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of waste gas treatment, and in particular relates to the field of preparation of lignin-based porous carbon. Background Art
[0002] Excessive consumption of fossil energy has produced a large amount of CO2, causing urgent environmental problems such as global warming, rising sea levels, and declining air quality. The most critical link in achieving carbon emission reduction is carbon capture and storage (CCUS).
[0003] Porous carbon has the advantages of high specific surface area, large pore volume, rich pore structure, strong hydrophobicity, good physical and chemical stability, and low density. It is widely used in energy storage, adsorption separation, catalysis, etc. Studies have shown that the CO2 capture performance of porous carbon is mainly determined by two aspects of the structure. The first is the pore structure. Porous carbon has abundant ultra-micropores (d<0.7nm) and can increase the adsorption of CO2 through micropore filling mechanism under low pressure conditions. In addition, the pore shape and size of porous carbon are 3-10 times that of the target molecule CO2 (0.33nm), and CO2 can be selectively adsorbed at the flue port of the mixed gas. The second is the surface chemical properties. Various heteroatoms (N, O, S, P, etc.) are doped to regulate the chemical structure of porous carbon and increase the adsorption capacity and selectivity of CO2. Nitrogen-containing groups (such as pyrrolic nitrogen, pyridinic nitrogen, etc.) in the porous carbon skeleton can strengthen the interaction between CO2 molecules and the pore surface through acid-base interactions, electrostatic (quadrupole) interactions, and hydrogen bonding interactions, thereby improving the selective adsorption effect of CO2. The oxygen-containing functional groups (such as ether and hydroxyl groups) of porous carbon mainly improve the CO2 adsorption performance through charge interaction. Therefore, the precise regulation of the pore structure and chemical structure of porous carbon materials is an extremely important technical bottleneck for the efficient adsorption of CO2.
[0004] Lignin molecules are a three-dimensional network of high molecular weight aromatic polymers formed by three phenylpropane units connected by ether bonds and carbon-carbon bonds, which contain abundant functional groups such as carboxyl, hydroxyl, ether bonds and methoxyl groups. Moreover, lignin has the advantages of being cheap, easy to obtain, environmentally friendly and sustainable, and having a wide range of sources. Therefore, it is promising to use lignin-based residues from the bioethanol process to prepare porous carbon with rich structure and stable performance.
[0005] At present, the preparation methods of lignin-based modified carbon materials mainly include activation method, template method, hydrothermal method, molten salt method and microwave heating method. The pretreatment of the precursor, the addition of nitrogen-containing substances and the combination of preparation technology will have an important influence on the structure of porous carbon. Patent application CN109761234A discloses a preparation method of nitrogen-rich porous lignin-based carbon material, which uses waste biomass resources such as bark, straw, food residues, etc. as raw materials, first pre-carbonizes the raw materials and nitrogen source, and then mixes the pre-carbonized product with alkali and ball mills and then carbonizes at high temperature to obtain a nitrogen-rich porous wood-based carbon material with high active centers and developed pore structure, but this method requires two carbonizations and high temperature energy consumption. Patent application CN110316717B discloses a preparation method and application of a nitrogen-containing porous carbon material. First, lignin, a nitrogen source, and a low eutectic salt are mixed by ball milling, and then the mixture is carbonized at high temperature to obtain a nitrogen-containing carbon material. Although the preparation method is simple and easy to operate, the specific surface area of the material is low and the CO2 adsorption capacity is also low. The specific CO2 adsorption capacity is 3.90-4.35mmol / g. Patent application CN115215320A discloses a supramolecular induced nitrogen-doped lignin-derived carbon material and its preparation method and application. Sodium lignin sulfonate and melamine are mixed and then cyanuric acid is added to obtain a solid, and then the solid is pyrolyzed to obtain a nitrogen-doped lignin-derived carbon material. However, a large amount of toxic, irritating, and expensive cyanuric acid is consumed, and the pore structure of the obtained carbon material lacks regulation. Its specific surface area is 1094.5-1342.5m 2 / g, which is only a medium value among existing biomass-based carbon materials.
[0006] In view of the actual production problems in the above-mentioned preparation process, such as toxic and high-cost reagents, high process energy consumption and low CO2 adsorption, as well as the structural defects of biomass-based carbon materials obtained by the corresponding preparation method, the present invention aims to propose a method for preparing green and low-cost lignin-based porous carbon with high specific surface area, high nitrogen and oxygen heteroatom content and adjustable pore structure, and the obtained material has excellent CO2 capture performance. Summary of the invention
[0007] In response to the problem that the existing lignin-based carbon materials have unsatisfactory carbon dioxide capture capacity and selectivity, the present invention provides a new method for preparing nitrogen-containing and oxygen-rich lignin-based porous carbon, aiming to prepare materials with excellent carbon dioxide adsorption capacity and selectivity.
[0008] The second purpose of the present invention is to provide nitrogen-containing and oxygen-rich lignin-based porous carbon prepared by the preparation method and its application in carbon dioxide adsorption.
[0009] In view of the problems of unsatisfactory carbon dioxide adsorption capacity and selectivity in the prior art, the present invention provides the following solutions, specifically:
[0010] A method for preparing nitrogen-containing oxygen-rich lignin-based porous carbon, comprising subjecting an aqueous solution containing a lignin raw material and a nitrogen source to hydrothermal treatment to obtain a hydrothermal product, wherein the hydrothermal temperature is 100 to 250° C., and the nitrogen source is at least one of melamine, ethylenediamine, and urea;
[0011] The hydrothermal product and the activator are mixed and subjected to tabletting treatment to obtain discs, and the discs are then heat-treated in a protective atmosphere to obtain the nitrogen-containing and oxygen-rich lignin-based porous carbon;
[0012] In the tableting stage, the weight ratio of the hydrothermal product to the activator is 1:1.5-5; the pressure is 15-25 MPa;
[0013] The temperature of the heat treatment is 550-800°C.
[0014] In the present invention, the lignin raw material is innovatively subjected to hydrothermal treatment with the assistance of the nitrogen source, and then tableted together with the activator and heat treated, and further coordinated with the joint control of hydrothermal parameters, tableting parameters and heat treatment parameters, so that synergy can be achieved, and a microstructure and surface active groups adapted to carbon dioxide can be constructed, so that the adsorption capacity and adsorption selectivity of carbon dioxide can be synergistically improved.
[0015] The lignin raw material described in the present invention can be any material containing lignin in the industry, for example, a raw material containing at least one of enzymatic lignin, organic solvent lignin, alkali lignin, and DES extracted lignin. For example, the lignin raw material can be the residue containing lignin produced by bioethanol preparation.
[0016] In the present invention, the nitrogen source-assisted hydrothermal, activator-assisted tableting, and joint control of heat treatment operations and parameters are the key to the synergistic construction of microstructures and active groups adapted to carbon dioxide; on this basis, further coordinated control of nitrogen source type, hydrothermal temperature, activator type, tableting parameters, and heat treatment parameters is helpful to further facilitate the construction of microstructures and active groups adapted to carbon dioxide, and to further synergistically improve the capacity and adsorption selectivity of carbon dioxide.
[0017] Preferably, the nitrogen source is melamine. In the present invention, melamine is used as the nitrogen source, and in combination with the preparation process of the present invention, the adsorption and adaptation effect of the material on carbon dioxide can be further improved.
[0018] Preferably, the weight ratio of the lignin raw material to the nitrogen source is 0.5 to 4:1, more preferably 1 to 1.5:1;
[0019] Preferably, in the starting aqueous solution of the hydrothermal treatment, the mass ratio of the lignin raw material to water is 1:5-20, more preferably 1:10-15.
[0020] Preferably, the temperature of the hydrothermal treatment is 140 to 180°C, more preferably 140 to 160°C;
[0021] Preferably, the hydrothermal treatment time is 5 to 30 hours; more preferably 15 to 20 hours.
[0022] Preferably, after the hydrothermal treatment is completed, the solid and liquid are separated, the solid is washed with alcohol and acid, and then washed with water until neutral, and then dried before proceeding to the subsequent steps.
[0023] In the present invention, under the combined control of the nitrogen source-assisted hydrothermal and process parameters, it is further subjected to tableting treatment together with the active agent, and further coordinated with the combined control of the tableting parameters, which is beneficial to constructing a carbon dioxide-adapted microstructure and active sites, thereby facilitating the carbon dioxide adsorption capacity and adsorption selectivity.
[0024] Preferably, the activator is at least one of KOH, ZnCl2, NaOH, and K2CO3.
[0025] Preferably, the mass ratio of the hydrothermal product to the activator is 1:2-4.
[0026] In the present invention, the hydrothermal product and the activator are mixed by grinding;
[0027] Preferably, the tabletting method is mechanical pressing;
[0028] Preferably, the pressing pressure in the tableting stage is 18 to 22 MPa.
[0029] Preferably, the compression time in the tableting stage is 0.5 to 50 min, preferably 1 to 40 min, and more preferably 10 to 40 min.
[0030] In the present invention, the tablet is subjected to subsequent heat treatment, and further coordinated with the joint control of heat treatment parameters such as temperature, so as to synergistically construct an adsorption structure and active sites with a carbon dioxide adaptation degree, which is more conducive to the adsorption capacity and selectivity of carbon dioxide.
[0031] Preferably, the temperature of the heat treatment is 600-700° C., and more preferably 600-650° C. It is found that under the process of the present invention, further synergy can be achieved through the combined control of the temperature, and the adaptability of the prepared material to carbon dioxide adsorption can be further improved, and the adsorption capacity and selectivity can be further improved.
[0032] Preferably, the heat treatment time is 0.5 to 4 hours, preferably 1 to 2 hours;
[0033] Preferably, after the heat treatment, the nitrogen-containing and oxygen-rich lignin-based porous carbon is obtained by washing with acid solution, washing with water until neutrality and then drying.
[0034] The present invention also provides a nitrogen-containing oxygen-rich lignin-based porous carbon prepared by the preparation method, which has a hierarchical pore structure of micropores, mesopores and macropores, with micropore and mesopore contents of 53.9-77.3% and 18.6-42.5% respectively, and a specific surface area of 900-2000m 2 / g, nitrogen content is 1.5-2.0%, and oxygen content is 30-55%.
[0035] The present invention also provides an application of the nitrogen-containing and oxygen-rich lignin-based porous carbon obtained by the preparation method as a gas adsorption material; preferably, as a carbon dioxide adsorption material.
[0036] Beneficial effects:
[0037] 1. The present invention innovatively hydrothermally treats the lignin raw material with the assistance of the nitrogen source, and then heat treats it after tableting with the active agent, and further coordinates the joint control of hydrothermal parameters, tableting parameters and heat treatment parameters, so that synergy can be achieved, and a microstructure and surface active groups adapted to carbon dioxide can be constructed, which can synergistically improve the adsorption capacity and adsorption selectivity of carbon dioxide.
[0038] 2. The material prepared by the preparation method of the present invention has excellent adsorption capacity and selectivity for CO2.
[0039] 3. The raw materials of the present invention are widely available, low in cost, green and environmentally friendly, and have the advantages of good promotion and high-value co-production. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the specific implementation of the present invention or the technical solution in the prior art, the drawings required for use in the specific implementation or the description of the prior art are briefly introduced below.
[0041] Figure 1 This is a SEM image of the nitrogen-containing and oxygen-rich hierarchical porous carbon material (LDD-PT-K) prepared in Example 3;
[0042] Figure 2 This is the pore size distribution diagram of the nitrogen-containing oxygen-rich hierarchical porous carbon material (LDD-PT-K) prepared in Example 3;
[0043] Figure 3 The adsorption isotherms of CO2 of the porous carbon materials prepared in Examples 1 and 2 at 273K;
[0044] Figure 4 The adsorption isotherms of CO2 of the porous carbon materials prepared in Examples 3 and 4 at 273K;
[0045] Figure 5 The adsorption isotherms of CO2 of the porous carbon materials prepared in Examples 3 and 5 at 273K;
[0046] Figure 6 The adsorption isotherms of the porous carbon materials prepared in Examples 4a and 6 for CO2 at 273K;
[0047] Figure 7 The adsorption isotherms of CO2 of the porous carbon materials prepared in Example 4a and Comparative Examples 1-3 at 273K;
[0048] Figure 8 Henry selectivity of CO2 / N2 of the nitrogen-containing and oxygen-rich hierarchical porous carbon material (LDD-C-1) prepared in Example 4a at 273K and 1.0 bar. DETAILED DESCRIPTION
[0049] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0050] If no specific conditions are specified in the examples of the present invention, the conventional conditions or the conditions recommended by the manufacturer are used. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased from the market.
[0051] The CO2 and N2 adsorption isotherms of carbon materials were measured at 273 K using the ASAP2020 analyzer from McMerritt Instruments, Inc., USA. The pressure range of CO2 or N2 was from 0.02 to 1.0 bar. Before the test, the carbon materials were degassed at 150 °C for 3 h to remove the guest molecules in the pores. After the samples were cooled to room temperature, CO2 or N2 gas was introduced.
[0052] Example 1
[0053] (1) 3 g of enzymatically hydrolyzed lignin, 3 g of melamine (nitrogen source) and 30 ml of deionized water were mixed and ultrasonicated for half an hour to obtain a dispersion, which was poured into a stainless steel autoclave and kept at 150°C (marked as T1) for 20 hours. The obtained solid was washed alternately with ethanol, 5% hydrochloric acid and deionized water until neutral, and dried to obtain nitrogen-doped hydrothermal carbon.
[0054] (2) 1.5 g of hydrothermal charcoal and 6 g of sodium hydroxide (activator) were mixed in an agate mortar and ground thoroughly. The mixture was then compacted at a pressure of 20 MPa for 1 min using a tablet press to obtain a mixture disc.
[0055] (3) Under nitrogen atmosphere, the disc was placed in a tube furnace and heated to 800°C at a rate of 3°C / min and retained at 800°C (marked as T2) for 1 h. It was then washed with 10% hydrochloric acid and deionized water until neutral and dried to obtain nitrogen-containing oxygen-rich hierarchical porous carbon, named LDD-N-1.
[0056] (4) The CO2 adsorption capacity of the obtained sample LDD-N-1 at 273K and 1bar is 3.7mmol / g.
[0057] Example 2
[0058] Compared with Example 1, the only difference is that in step (1), the type of nitrogen source is changed, and the experimental groups are:
[0059] Group A: The nitrogen source was urea, named LDD-N-2;
[0060] Group B: The nitrogen source was ethylenediamine, named LDD-N-3;
[0061] Comparative group A: The nitrogen source was acetamide, named LDD-N-4;
[0062] The carbon dioxide adsorption was measured in the manner of Example 1, and the results were:
[0063] Group A: The CO2 adsorption capacity of the obtained sample LDD-N-2 at 273K and 1bar is 3.5mmol / g;
[0064] Group B: The CO2 adsorption capacity of the obtained sample LDD-N-3 at 273K and 1bar is 3.6mmol / g, and the calculated Henry selectivity is 17.3;
[0065] Comparison with Group A: The CO2 adsorption capacity of the obtained sample LDD-N-4 at 273K and 1bar is 2.7mmol / g.
[0066] Example 3
[0067] (1) 3 g of enzymatically hydrolyzed lignin, 3 g of melamine (nitrogen source) and 30 ml of deionized water were mixed and ultrasonicated for half an hour to obtain a dispersion, which was poured into a stainless steel autoclave and kept at 150°C (marked as T1) for 20 hours. The obtained solid was washed alternately with ethanol, 5% hydrochloric acid and deionized water until neutral, and dried to obtain nitrogen-doped hydrothermal carbon.
[0068] (2) 1.5 g of hydrothermal carbon and 6 g of sodium hydroxide (activator) were mixed in an agate mortar and ground thoroughly, and then compacted at a pressure of 20 MPa for 20 min using a tablet press to obtain a mixture disc.
[0069] (3) Under nitrogen atmosphere, the disc was placed in a tube furnace and heated to 600 °C at a rate of 3 °C / min and kept at 600 °C (marked as T2) for 1 h. It was then washed with 10% hydrochloric acid and deionized water until neutral and dried to obtain nitrogen-containing oxygen-rich hierarchical porous carbon, named LDD-PT-K.
[0070] (4) The CO2 adsorption capacity of the obtained sample LDD-PT-K at 273K and 1bar is 5.0mmol / g.
[0071] Example 4
[0072] Compared with Example 3, the only difference is that the pressure and time of step 2 are changed to:
[0073] Group A: The pressure application time was 10 min, named LDD-T-1 (also known as LDD-C-1);
[0074] Group B: The pressure application time was 40 min, named LDD-T-2;
[0075] Group C: applied pressure was 25 MPa;
[0076] Group D: applied pressure was 15 MPa;
[0077] Comparative group A: pressure 40MPa, named LDD-P-1;
[0078] Comparative group B: pressure was 10 MPa, named LDD-P-2;
[0079] The carbon dioxide adsorption performance was measured in the manner of Example 3, and the results were:
[0080] Group A: The CO2 adsorption capacity of the obtained sample LDD-T-1 at 273K and 1bar is 4.7mmol / g, and the calculated Henry selectivity is 28.9;
[0081] Group B: The CO2 adsorption capacity of the obtained sample LDD-T-2 at 273K and 1bar was 4.6mmol / g;
[0082] Group C: The CO2 adsorption capacity of the obtained product at 273K and 1bar is 4.5mmol / g;
[0083] Group D: The CO2 adsorption capacity of the obtained product at 273K and 1bar is 4.4mmol / g;
[0084] Comparative group A: The CO2 adsorption capacity of the obtained sample LDD-P-1 at 273K and 1 bar is 3.0mmol / g.
[0085] The calculated Henry selectivity is 10.6;
[0086] Comparative Group B: The CO2 adsorption capacity of the obtained sample LDD-P-2 at 273K and 1 bar is 3.3 mmol / g; Example 5
[0087] Compared with Example 3, the only difference is that the amount of activator in step 2 is changed to:
[0088] Group A: The dosage of activator was 3 g, named LDD-K-1;
[0089] Comparative group A: The amount of activator used was 9 g, named LDD-K-2.
[0090] The carbon dioxide adsorption performance was measured in the manner of Example 3, and the results were:
[0091] Group A: The CO2 adsorption capacity of the obtained sample LDD-K-1 at 273K and 1bar was 5.1mmol / g;
[0092] Comparative group A: The CO2 adsorption capacity of the obtained sample LDD-K-1 at 273K and 1 bar is 1.7 mmol / g.
[0093] Example 6
[0094] Compared with Example 4a, the only difference is that T2 in step 3 is changed to:
[0095] Group A: The temperature of T2 is 700°C, named LDD-C-2;
[0096] Comparative group A: The temperature of T2 was 500°C, named LDD-C-3;
[0097] Comparative Example B: The temperature of T2 is 850°C, named LDD-C-4;
[0098] The carbon dioxide adsorption performance was measured in the manner of Example 4a, and the results were:
[0099] Group A: The CO2 adsorption capacity of the obtained sample LDD-C-2 at 273K and 1bar is 4.1mmol / g, and the calculated Henry selectivity is 20.3;
[0100] Comparative group A: The CO2 adsorption capacity of the obtained sample LDD-C-3 at 273K and 1bar was 2.4mmol / g;
[0101] Comparative group B: The CO2 adsorption capacity of the obtained sample LDD-C-4 at 273K and 1 bar is 2.6 mmol / g.
[0102] Comparative Example 1
[0103] Compared with Example 4a, the difference is that the hydrothermal treatment in step (1) is not performed, but 1.5 g of lignin and 1.5 g of melamine are used to replace the hydrothermal charcoal in step (2) to participate in step (2) and subsequent steps. The obtained sample is named LDD-1.
[0104] The results are: the CO2 adsorption amount at 273K and 1 bar is 3.3mmol / g, and the calculated Henry selectivity is 9.7.
[0105] Comparative Example 2
[0106] Compared with Example 4a, the only difference is that no tableting treatment is performed, and the ground mixture of hydrothermal charcoal and activator is treated in step (3). The obtained sample is named LDD-2.
[0107] The results are: the CO2 adsorption amount at 273K and 1bar is 3.3mmol / g.
[0108] Comparative Example 3
[0109] Compared with Example 4a, the difference is that the hydrothermal treatment of step (1) and the tableting treatment are not carried out, but the ground mixture of 1.5g lignin, 1.5g melamine and activator is treated in step (3), and the obtained sample is named LDD-3.
[0110] The results showed that the CO2 adsorption capacity at 273K and 1 bar was 3.8 mmol / g, which was significantly different from that of Example 4a.
[0111] Comparative Example 4
[0112] Compared with Example 4a, the only difference is that no activator is added in the tableting stage, but in step 3, the tablets without activator and the activator are mixed and then subjected to T2 heat preservation treatment.
[0113] The results are: the CO2 adsorption amount at 273K and 1bar is 3.2mmol / g.
[0114] Comparative Example 5
[0115] Compared with Example 4a, the only difference is that no activator is added in the tableting stage, the obtained discs are directly subjected to heat treatment at temperature T2 in step 3, the product obtained by heat treatment is mixed with an equal amount of activator, and then heat treated at T2 to obtain the final product.
[0116] The results are: the CO2 adsorption amount at 273K and 1bar is 3.4mmol / g.
Claims
1. A method for preparing nitrogen-containing oxygen-rich lignin-based porous carbon for carbon dioxide adsorption, characterized in that: The aqueous solution containing lignin raw material and nitrogen source is subjected to hydrothermal treatment to obtain a hydrothermal product, wherein the hydrothermal temperature is 100-250° C., the nitrogen source is at least one of melamine, ethylenediamine and urea; and the weight ratio of the lignin raw material to the nitrogen source is 0.5-4:1; The hydrothermal product and the activator are mixed and subjected to tabletting treatment to obtain discs, and the discs are then heat-treated in a protective atmosphere to obtain the nitrogen-containing and oxygen-rich lignin-based porous carbon; In the tableting stage, the weight ratio of the hydrothermal product to the activator is 1:1.5~5; the pressure is 15~25MPa; the pressing time in the tableting stage is 0.5~50 min; The heat treatment temperature is 550~800℃.
2. The preparation method according to claim 1, characterized in that The lignin raw material comprises at least one of enzymatic lignin, organic solvent lignin, alkali lignin and DES extracted lignin.
3. The preparation method according to claim 1, characterized in that: In the starting aqueous solution of the hydrothermal treatment, the mass ratio of the lignin raw material to water is 1:5-20.
4. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal treatment is 140~180℃; The hydrothermal treatment time is 5 to 30 hours; After the hydrothermal treatment, the solid and liquid are separated, and the solid is washed with alcohol and acid, and then washed with water until it is neutral and dried before proceeding to the subsequent steps.
5. The preparation method according to claim 1, characterized in that: The activator is at least one of KOH, ZnCl2, NaOH and K2CO3.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the hydrothermal product to the activator is 1:2-4.
7. The preparation method according to claim 1, characterized in that: The hydrothermal product and the activator are mixed by grinding.
8. The preparation method according to claim 7, characterized in that: The tableting method is mechanical compression.
9. The preparation method according to claim 7, characterized in that: The compression time during the tableting stage is 1 to 40 minutes.
10. The preparation method according to claim 1, characterized in that: The temperature of heat treatment is 600~700℃.
11. The preparation method according to claim 1, characterized in that: The heat treatment temperature is 600~650℃.
12. The preparation method according to claim 1, characterized in that: The heat treatment time is 0.5~4 h.
13. The preparation method according to claim 1, characterized in that: After the heat treatment, the product is washed with acid solution, washed with water until neutrality and then dried to obtain the nitrogen-containing and oxygen-rich lignin-based porous carbon.
14. A nitrogen-containing and oxygen-rich lignin-based porous carbon prepared by the preparation method according to any one of claims 1 to 13, characterized in that: It has a hierarchical pore structure of micropores, mesopores and macropores. The micropore and mesopore contents are 53.9~77.3% and 18.6~42.5% respectively, and the specific surface area is 900~2000 m 2 / g, nitrogen content is 1.5~2.0%, and oxygen content is 30~55%.
15. An application of nitrogen-containing oxygen-rich lignin-based porous carbon prepared by the preparation method according to any one of claims 1 to 13, characterized in that: It is used as an adsorbent for carbon dioxide.
Citation Information
Patent Citations
Preparation method of nitrogen-rich porous wood-based carbon material
CN109761234A
A method for preparing nitrogen-containing porous carbon materials and their applications
CN110316717B
Supramolecular induced nitrogen-doped lignin derived carbon material as well as preparation method and application thereof
CN115215320A
Method for preparing high-performance porous carbon material from organic solid wastes through nitrogen-doping hydrothermal operation and activation
CN110342512A
Porous activated carbon and preparation method thereof
CN113233455A